Let $f(x)$ be a function in a variable $x$. In differential calculus, the differentiation of the function $f(x)$ with respect to $x$ is written in the following mathematical form.

$\dfrac{d}{dx}{\, f(x)}$

For deriving the derivative of a constant multiple function with respect to a variable, we must know the fundamental definition of the differentiation of a function in limit form.

According to the definition of the derivative, the derivative of a function $f(x)$ with respect to $x$ can be written in limit form.

$\dfrac{d}{dx}{\, f(x)}$ $\,=\,$ $\displaystyle \large \lim_{\Delta x \,\to\, 0}{\normalsize \dfrac{f(x+\Delta x)-f(x)}{\Delta x}}$

If we take the change in variable $x$ is equal to $h$, which means $\Delta x = h$, then the equation can be expressed in terms of $h$ as follows.

$\implies$ $\dfrac{d}{dx}{\, f(x)}$ $\,=\,$ $\displaystyle \large \lim_{h \,\to\, 0}{\normalsize \dfrac{f(x+h)-f(x)}{h}}$

Let $k$ be a constant, then the product of constant $k$ and the function $f(x)$ is called the constant multiple function, which is written in product form as $k.f(x)$ mathematically.

Take, the constant multiple function is denoted by $g(x)$. Therefore, $g(x) = k.f(x)$. Now, write the differentiation of $g(x)$ with respect to $x$ in limit form as per the definition of the derivative.

$\dfrac{d}{dx}{\, g(x)}$ $\,=\,$ $\displaystyle \large \lim_{h \,\to\, 0}{\normalsize \dfrac{g(x+h)-g(x)}{h}}$

In this case, $g(x) = k.f(x)$ then $g(x+h) = k.f(x+h)$. Now, substitute them in the above equation.

$\implies$ $\dfrac{d}{dx}{\, g(x)}$ $\,=\,$ $\displaystyle \large \lim_{h \,\to\, 0}{\normalsize \dfrac{k.f(x+h)-k.f(x)}{h}}$

$\implies$ $\dfrac{d}{dx}{\, \Big(k.f(x)\Big)}$ $\,=\,$ $\displaystyle \large \lim_{h \,\to\, 0}{\normalsize \dfrac{k.f(x+h)-k.f(x)}{h}}$

$k$ is a common factor in the expression of the numerator of the function and it can be taken out as a common factor from the terms as per the factorization by taking out the common factors.

$\implies$ $\dfrac{d}{dx}{\, \Big(k.f(x)\Big)}$ $\,=\,$ $\displaystyle \large \lim_{h \,\to\, 0}{\normalsize \dfrac{k\Big(f(x+h)-f(x)\Big)}{h}}$

Now, factorize the function for separating the constant.

$=\,\,\,$ $\displaystyle \large \lim_{h \,\to\, 0}{\normalsize \Bigg[k \times \Bigg(\dfrac{f(x+h)-f(x)}{h}\Bigg) \Bigg]}$

It can be further simplified by the product rule of limits.

$=\,\,\,$ $\displaystyle \large \lim_{h \,\to\, 0}{\normalsize (k)}$ $\times$ $\displaystyle \large \lim_{h \,\to\, 0}{\normalsize \dfrac{f(x+h)-f(x)}{h}}$

Now, evaluate the limit of the constant by the direct substitution method.

$=\,\,\,$ $k \times \displaystyle \large \lim_{h \,\to\, 0}{\normalsize \dfrac{f(x+h)-f(x)}{h}}$

According to the fundamental definition of the derivative, the limit of the second function is the differentiation of the function $f(x)$.

$=\,\,\,$ $k \times \dfrac{d}{dx}{\, f(x)}$

$\,\,\, \therefore \,\,\,\,\,\,$ $\dfrac{d}{dx}{\, \Big(k.f(x)\Big)}$ $\,=\,$ $k.\dfrac{d}{dx}{\, f(x)}$

Therefore, it is proved that the derivative of a constant multiple function with respect to a variable is equal to the product of the constant and the derivative of the function.

Latest Math Topics

Dec 13, 2023

Jul 20, 2023

Jun 26, 2023

Latest Math Problems

Jan 30, 2024

Oct 15, 2023

Copyright © 2012 - 2023 Math Doubts, All Rights Reserved